Influencia de las redes sociales en la semántica y redacción de los adolescentes del Sector Agrilsa del cantón Quevedo en el año 2020 - Molina Domiguez, Ana Zulay (2021)
New technologies have brought many benefits to the human being, but with this it has also caused wear and tear to the correct use of language, due to complete freedom in semantics and writing, transgressing norms, creating and transmitting rude and violent content. Transforming the writing model using terms that are commonly used in citizenship and even more so in adolescents who often choose to misuse semantics more quickly The current situation of adolescents, specifically in the Agrilsa Sector of the Quevedo canton, affects grammar, due to the use of social networks and these damage language. At the end of the investigation, he agrees that, ultimately, the above is correct. The methodology applied in the research was through the qualitative method that focused on the collection of data through the surveys carried out with the adolescents of the Agrilsa Sector, resulting in a negative answer, since the adolescent is not interested in the correct use of the semantics or their writing, they are interested in their communication flowing and being understood, making grammatical rules of little use.